ANALISIS TINGKAT PEMAHAMAN ORANG TUA DALAM KESADARAN PENGGUNAAN MEDIA SOSIAL YANG BERDAMPAK TERHADAP KEJAHATAN DAN KEKERASAN PADA ANAK - Syafnita, Tisna (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The background of this research is that the development of increasingly advanced technology, especially social media, can have a negative impact on children, both directly and indirectly. The most common negative effects are harassment, cyberbullying and pornographic content, which not only adults but also children can access without parental supervision. This study uses surveys or questionnaires that are distributed online to parents who have early childhood to determine parents' understanding of the impact of using social media. From the questionnaire, information was obtained that most parents like to post photos of their children on social media because they do not know the negative impact of posting photos of their children on social media. In addition, the average parent agrees to prohibit their child from using social media, and children whose parents allow social media do not know their child's social media password. Furthermore regarding cyberbullying, the average respondent's parents stated that their child had never been a victim of cyberbullying because the child had never reported being a victim of cyberbullying on social media, but parents were very aware of the crime of cyberbullying. The survey also found that on average parents are aware of forms of child sexual abuse and exploitation online, such as sexting, sending pornographic images or videos to victims, and other forms of social media crime.